Non-puerperal uterine inversion: first case reported in Peru - Aguilar-Cieza, Aldo (2021)
Non-puerperal uterine inversion is very rare. A case associated with leiomyomatosis is reported. The case of a 45-year-old multiparous woman with severe vaginal bleeding, pelvic pain and vaginal foreign body sensation is presented. Uterine leiomyoma in abortive phase was diagnosed. She was scheduled for myomectomy with probable abdominal hysterectomy and complete uterine inversion was found. This report is an anecdotal case of non-puerperal uterine inversion, whose surgical treatment was successful.